Penerapan Pembelajaran Team Games Tournament (TGT) pada Materi Garis dan Sudut: Dampak Hasil Belajar - Fitriani, Desy; Pancarita; Punding, Walter (Lembaga Bale Literasi, 2024)
This study was prompted by the low scores students obtained on the topic of lines and angles in Grade VII at MTsS Hidayatul Insan, Palangka Raya. The aim of this research is to describe the students' learning outcomes after the implementation of the Team Games Tournament (TGT) method on the lines and angles topic in Grade VII. The subjects of this study were Grade VII students in the second semester at MTsS Hidayatul Insan, Palangka Raya, during the 2019/2020 academic year. This research employed a quantitative approach with a descriptive research design. The instrument used was a learning outcomes test sheet. Student performance was measured through a final test administered to 22 students, of which 19 students achieved scores above the minimum competency criterion (KKM) of 65, indicating successful completion, while 3 students did not meet this criterion. The overall achievement level was 74.54%, meaning that the students' comprehension of the material was ≥65%, categorized as